Civil and social death: criminal background and the loss of the self - Henley, Andrew (Routledge, 2018)
In this chapter I offer an alternative perspective to the themes of ‘dying’, ‘loss’ and bereavement’ within criminal justice and explore the relationships which exist between social practices of punishment and the status or positioning of former lawbreakers who have been punished . First, I provide a brief history of punishments in England whose object was to bring about not only the literal death of the condemned person but also their ‘civil death’. Second, I connect these historical practices of juridical ‘othering’ to the ‘pains of criminalisation’ which exist in the present. These, I argue, are manifestations of ‘social death’ which are experienced by people with convictions due to the stigma of having a criminal record. Drawing on Erving Goffman, I then suggest that this ‘mortification of the self’ disrupts pre-and post-conviction social identity in ways which require us to develop wider conceptions of ‘loss’ and ‘bereavement’ in criminal justice research.